2018
DOI: 10.1111/vox.12669
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour and perception of illness: modulating variables of adherence in patients with haemophilia

Abstract: Adherence in haemophilia requires a more experiential approach and individualized education. It is important that professionals take into account the patient's perception, behaviour and attitude towards the disease to achieve a better adaptation of their coping resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Level of adherence to prophylaxis in haemophilia has also not been examined so far in Eastern European countries. Data for the adherence level from USA, Canada, Australia and Western European countries have been found to vary from 44% to 87% 5‐10 . Our data indicated that 83% of the sample was adherent.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Level of adherence to prophylaxis in haemophilia has also not been examined so far in Eastern European countries. Data for the adherence level from USA, Canada, Australia and Western European countries have been found to vary from 44% to 87% 5‐10 . Our data indicated that 83% of the sample was adherent.…”
Section: Discussionmentioning
confidence: 57%
“…Data for the adherence level from USA, Canada, Australia and Western European countries have been found to vary from 44% to 87%. [5][6][7][8][9][10] Our data indicated that 83% of the sample was adherent. In line with previous findings that depression is an important factor for adherence in many chronic diseases including haemophilia, 9,[11][12][13][14][15][16][17][18][19][20][21][22]…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, a rapidly growing body of studies has shown that illness perceptions have been associated with coping strategies and behaviors adopted by patients in order to manage their disease (Leventhal et al, 1980;Hagger & Orbell, 2003;French et al, 2006;Kucukarslan, 2012;Richardson et al, 2017b). Although the scope of this review is not to investigate interesting associations between illness perceptions and coping, some studies have provided evidence about the important role of the former in medication adherence among patients with hematologic disorders, such as hemophilia (Llewellyn et al, 2003;Lamiani et al, 2015;Torres-Ortuño et al, 2018) and sickle cell anemia (Atorkey et al, 2017;Badawy et al, 2017;Oudin-Doglioni et al, 2019). This review is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the quality of life of patients with haemophilia can be affected by the uncertainty of the chronic disease, the lack of adherence to medical and pharmacological prescriptions and the incidence of haemorrhagic episodes 5. Prophylactic approaches have demonstrated to reduce in 53% the incidence of haemorrhagic complications of patients with haemophilia, and if these appear, early interventions can reduce their adverse effects on the patient’s general health and quality of life 5–7…”
Section: Introductionmentioning
confidence: 99%